Georgia : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Georgian antimoney laundering (AML) and combating the financing of terrorism (CFT) regime has significantly improved since 2007. However, technical deficiencies, poor implementation, and limited resources undermine the effectiveness of the financial intelligence unit (FIU) and AML/CFT supervision. The country has a comprehensive legal framework in place criminalizing both ML and FT as autonomous offenses and no shortcomings have been identified. It has also established a framework to implement the relevant United Nations Security Council Resolutions (UNSCRs).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet